Proceedings of the Second (2015) ACM Conference on Learning @ Scale 2015
DOI: 10.1145/2724660.2724670
|View full text |Cite
|
Sign up to set email alerts
|

PeerStudio

Abstract: Rapid feedback is a core component of mastery learning, but feedback on open-ended work requires days or weeks in most classes today. This paper introduces PeerStudio, an assessment platform that leverages the large number of students' peers in online classes to enable rapid feedback on in-progress work. Students submit their draft, give rubricbased feedback on two peers' drafts, and then receive peer feedback. Students can integrate the feedback and repeat this process as often as they desire. In MOOC deploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(15 citation statements)
references
References 27 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Relying on askers to set the standard for answers may ultimately inhibit the efficacy of Q&A as a learning platform. Gazan [10] separates askers into 'seekers'-those who interact with the community and engage in conversation about their questions, and 'sloths'-those who post their homework verbatim and interact no further. Interview participants were aware of these differing uses of the site, and changed their standard for a good answer based on whether the asker was looking for elaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on askers to set the standard for answers may ultimately inhibit the efficacy of Q&A as a learning platform. Gazan [10] separates askers into 'seekers'-those who interact with the community and engage in conversation about their questions, and 'sloths'-those who post their homework verbatim and interact no further. Interview participants were aware of these differing uses of the site, and changed their standard for a good answer based on whether the asker was looking for elaboration.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fraser et al presented CritiqueKit, a system that reduces the burden of providing feedback at scale by classifying feedback and providing recommendations to reviewers [7]. Kulkarni et al built PeerStudio, a platform for rubric-based peer assessment on open-ended, in-progress student work, and demonstrated that rapid feedback given through this system helped to improve overall quality of work [10]. These systems have been shown to be effective for reducing burden and increasing quality in peer review, and have great potential to improve feedback in informal spaces.…”
Section: Crowd Feedback In Learning Settingsmentioning
confidence: 99%
“…Several studies have leveraged example submissions to improve feedback. For instance, PeerStudio simultaneously presents an example of excellent work in the review interface [25]. While this bears a resemblance to Juxtapeer's design, it is limited in two critical ways.…”
Section: Related Work In Peer Reviewmentioning
confidence: 99%
“…Despite these benefits, peer review still faces a fundamental challenge: learners often do not give expert-quality feedback on their peers' work [25,27,53]. Ineffective feedback has substantial negative consequences; learners are less likely to revise their work [46], and may lower standards [52] or develop a false sense of confidence that degrades future performance because of undeserved praise [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation